1992
DOI: 10.1007/bf03008659
|View full text |Cite
|
Sign up to set email alerts
|

Regional anaesthesia in high-risk infants

Abstract: We were impressed with the number of problems reported by Webster et al., in their experience providing spinal anaesthesia for high-risk neonates, l Also we have encountered some complications and reviewed our experience over a four-year period.We attempted to perform spinal anaesthesia for inguinal hernia repair in 62 expremature infants with a mean weight of 2.9 kg and a mean postconceptual age of 42 wk. Tetracaine with epinephrine was used for all patients, usually in a dose of 0.4 mg. kg -1 and a minimum o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1993
1993
1995
1995

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 2 publications
0
1
0
Order By: Relevance
“…One study which showed that regional anaesthesia was used less commonly in paediatric cases than in adults (Morray et al 1993) raises the complex issue of anaesthesia decision making in terms of outcome. When faced with the choice of anaesthesia for inguinal herniotomy in an ex-premature infant with bronchopulmonary dysplasia (Bailey, Valley & Peacock 1992;Peutrell & Hughes 1994), it might be asked: what is the greater risk, neurological complications associated with regional blockade or apnoea and prolonged intubation following general anaesthesia?…”
Section: Evidence Of Neurological Damagementioning
confidence: 99%
“…One study which showed that regional anaesthesia was used less commonly in paediatric cases than in adults (Morray et al 1993) raises the complex issue of anaesthesia decision making in terms of outcome. When faced with the choice of anaesthesia for inguinal herniotomy in an ex-premature infant with bronchopulmonary dysplasia (Bailey, Valley & Peacock 1992;Peutrell & Hughes 1994), it might be asked: what is the greater risk, neurological complications associated with regional blockade or apnoea and prolonged intubation following general anaesthesia?…”
Section: Evidence Of Neurological Damagementioning
confidence: 99%